Patients' Adherence to Tenofovir for the Treatment of Hepatitis B: The Role of Clinical Pharmacists: Patients' Adherence to Tenofovir for the Treatment of Hepatitis B - Abbasinazari, Mohammad; Bayati, Nima; Sharifian, Afsaneh; Afzal, Golnaz; Saffaei, Ali; Sahraei, Zahra (Iranian Journal of Pharmaceutical Sciences, 2020)
Tenofovir is an antiviral agent prescribed for patients suffering from hepatitis B. It is associated with some side effects such as reduction in the level of patients’ adherence. The aim of this study was to evaluate the impact of clinical pharmacist consultation on patients’ adherence to the use of Tenofovir. In this prospective study, a total of 80 patients were enrolled into the study and were divided into two groups. Patients in group one, received their medication in a routine clinic manner, while patients in the second group, by clinical pharmacist intervention, received Tenofovir along with verbal and written tips about the drug dosage, side effects, drug interactions, food-drug interactions and administration. Finally, patients’ adherence to their medication was evaluated using a standard scale. Also, adverse drug reaction (ADR) occurrence and some laboratory parameters were recorded for further analysis. The patients' adherence to their medication was higher in case group than the control group in first three month of follow up. Moreover, lower ADRs were observed in patients who received clinical pharmacist consultation. It can be concluded that consultation provided by clinical pharmacist can lead to better adherence to Tenofovir usage, better therapeutic response and better tolerance of side effects.